The value of rating systems in credence goods markets - Silvia Angerer; Daniela Glätzle-Rützler; Wanda Mimra; Thomas Rittmannsberger; Christian Waibel (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2025)
In this paper, we experimentally investigate the effect of public consumer ratings on market outcomes in credence goods markets. Contrary to search or experience goods, consumers cannot evaluate all dimensions of trade for credence goods, which may inhibit the information and reputation-building value of public rating systems. We implement a market in which experts have an informational advantage over consumers with respect to the appropriate service level. The rating system takes the form of a five-star rating system as is common on online rating websites. The value of this rating system is compared in two different expert market settings: First, one in which consumers cannot rely on information from personal experience with the expert, reflecting markets in which consumer-expert interactions are often first-time and infrequent (e.g. specialist visits in healthcare markets). Second, one in which consumers have personal experience with the expert, reflecting markets in which consumer-expert interactions are frequent and repeated (e.g. general practitioner visits in healthcare markets). We find that the public rating system significantly improves market outcomes. Furthermore, a public rating system is a good substitute for personal experience information in terms of market efficiency and consumer surplus. Combined, however, we find no complementarity between public ratings and personal experience information, mainly due to the already high market efficiency in the presence of either one.
Keywords: C91; D82; I11; L15; 330; Credence goods; expert behavior; ratings; feedback; laboratory experiment